Hellenistic Dora: The Moldmade Bowls from the 1980 – 2000 Seasons - Rosenthal-Heginbottom, Renate (Journal of Hellenistic Pottery and Material Culture, 2022)
Presented are the Moldmade Bowls (MMBs) from twenty years of excavations at Tel Dor, directed by Ephraim Stern. Hellenistic Dora on the Carmel coast was part of Phoenicia. The material is divided into two parts, and the catalogue will include the previously published finds by the author and the remainder. The finds from the successive expedition, directed by A. Gilboa and I. Sharon, have been entrusted to S. D. Mermelstein, and the particular significance of Mermelstein’s work will be the results of the NAA analyses relevant not only for Dora but for the entire southern Levant. Yet, it must be borne in mind that for practical and economic restrictions, it will be out of question to use NAA for all excavated material, and classifications based on visual identification and on the study of motifs and patterns will still be indispensable.